To the Biography of the Woman Writer Nadezhda A. Lappo-Danilevskaia - Konstantin Yu. Lappo-Danilevskii (Studia Litterarum)
The paper checks and reviews a number of key moments in the generally accepted biography of Nadezhda Aleksandrovna Lappo-Danilevskaia (born Liutkevich; 1871–1951), one of the most popular women writers of prerevolutionary Russia and of the Russian emigration, — a biography based first of foremost on information that she herself supplied. It establishes the correct date of her birth (September 29, 1871) and the most plausible birthplace (Mogilev, not Kiev); information about her father’s career and her close relatives is also reported. Materials from various Russian and Western archives allow us to elucidate important episodes of her life, such as: her marriage to the composer Sergei Sergeevich Lappo-Danilevskii (1868–1957) and the birth of their children; her singing career; the censorship of her novel “Princess Mara” (1914); the history of the English translation of her novel “A Russian Gentleman” and of its two editions (both 1917; in New York and in London); her literary and theatrical contacts in exile. Finally the fate of Lappo-Danilevskaia’s memoirs, written in French, is considered; their whereabouts are currently unknown.